Integrating theory and practice through industrial site visits at PT INALUM - Arianti, Santi Febri (Institute of Computer Science (IOCS), 2025)
The industrial site visit to PT Indonesia Asahan Aluminium (INALUM) was conducted to bridge the gap between theoretical knowledge and practical applications in metallurgical engineering education. This study employed a descriptive-analytical approach to evaluate the effectiveness of the visit in enhancing students’ understanding of aluminum production processes, engagement levels, and career readiness. Data were collected through structured questionnaires and analyzed using both quantitative and qualitative methods. Results showed significant improvements in students’ comprehension of metallurgical processes, particularly the Hall-Héroult process, casting operations, and quality assurance practices. Engagement ratings across activities were consistently high, and career interest in the aluminum industry increased from 56% before the visit to 82% after. The findings highlight the value of experiential learning in aligning academic curricula with industry demands. Future studies could explore larger sample sizes, longitudinal impacts, and the inclusion of hands-on activities to further enhance learning outcomes and career aspirations. This research underscores the importance of industrial partnerships in preparing skilled and sustainability-conscious metallurgical engineers.